Effects of Menstruations on Academic Performance of Girls at Irise Institute Jinja - Phionah Aliganyira (Uganda Christian University, 2025)
The study examined the “Effects of menstruation on academic performance of girls at Irise institute Jinja.” The general objective was to examine both experiences of managing menstrual cycle and academic experiences among girls during menstrual cycle at Irise Institute Jinja and the specific objectives were to describe the experiences of girls in managing the menstrual cycle at Irise Institute Jinja and to find out the academic experiences among girls during menstrual cycle at Irise Institute Jinja. The research study was carried out in a non-government organization by the name of Irise Institute East Africa. The purpose of the study was to acquire more knowledge on the effects of menstruation on academic performance of girls and to also understand more on the strategies employed in mitigating menstrual related challenges. This research employed the empowerment theory in the finding of the answers to the research questions as well as achieving the research objectives. Empowerment theory (Dauglas, 2016) suggests that it is a process and a collective effort which involved individual participation in the activities and decision making. The exploratory research design was used for this research study together with qualitative approach for data collection. The research design helped the researcher to describe the experiences of girls in managing menstrual cycle and to find out the academic experiences among girls during menstrual cycle. The researcher concluded that menstruation period requires monthly education since it’s a monthly cycle preparing the girls, boys and teachers how to handle any of such a case, in some schools, NGOs take sex education programs to all students which prepares the girls both mentally and physically. It is true that sometimes the experiences are negative however, according to the research, there is hope that these negative experiences can be transformed to positives when these girls are given all ears and guidance in case they start the process.
Undergraduate research